2021
DOI: 10.1007/s10903-021-01287-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression Symptoms Before and During the COVID-19 Pandemic Among Two Asian American Ethnic Groups

Abstract: Asian Americans have experienced compounding stressors during the pandemic as a result of racial discrimination. We aim of to investigate the prevalence of depression symptoms among Asian Americans before and during the COVID-19 pandemic and examine differences based on socio-demographic factors. Data are from a cross-sectional study (N = 636) among Chinese and South Asian adults in Chicago collected between February and May 2020. One cohort of participants were surveyed from each ethnic group before the pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Similarly, a study conducted using the patient health questionnaire eight-item depression scale (PHQ-8) found that, during the pandemic, the prevalence of depression among the South Asians was three times higher than among the Chinese Americans (38% vs. 13%). 21 In addition, another study found that Vietnamese respondents were most vulnerable to mental distress. 22 These increases in mental health impacts can be attributed to stress due to migration and acculturation, somatization, stigmas surrounding mental health and use of mental health services, underrepresentation among the mental health care providers, lack of culturally informed interventions and social isolation, and increased racial discrimination amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted using the patient health questionnaire eight-item depression scale (PHQ-8) found that, during the pandemic, the prevalence of depression among the South Asians was three times higher than among the Chinese Americans (38% vs. 13%). 21 In addition, another study found that Vietnamese respondents were most vulnerable to mental distress. 22 These increases in mental health impacts can be attributed to stress due to migration and acculturation, somatization, stigmas surrounding mental health and use of mental health services, underrepresentation among the mental health care providers, lack of culturally informed interventions and social isolation, and increased racial discrimination amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that racial-ethnic harassment and discrimination is linked to depression, reduced self-esteem, anger, powerlessness, and other negative psychological effects (Lozano et al, 2021; Sanchez et al, 2018). While all the articles included in the present study described the psychological impact of harassment and violence, we have included discussion of 10 studies that specifically investigated health impacts of anti-Asian harassment, vandalism, and interpersonal violence on the physical and mental health of Asian Americans.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis suggested that South and Southeast Asian Americans reported higher levels of psychological distress than did East Asian Americans, a pattern that was consistent with some but not all previous studies. For example, in an analysis of survey data collected from Chinese American and South Asian American residents of Chicago ( 29 ), South Asian Americans reported significantly more depressive symptoms than did Chinese Americans during COVID-19. Another study of Asian Canadians had also found that mental health symptoms increased more among South Asian Canadians (along with Black and Muslim Canadians) compared to East Asian, Southeast Asian, and White Canadians ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 636 Chinese and South Asian American adults residing in Chicago found that depressive symptoms were significantly higher among those who were surveyed after the start of the COVID-19 pandemic than those who were surveyed prior to the start of the pandemic. Specifically, they found that South Asian American, men, and younger adults surveyed after the start of the pandemic reported more depressive symptoms compared to East Asian Americans, women, and older adults ( 29 ). Hyunh et al ( 26 ) found in their sample of 380 East and Southeast Asian American adults in Ohio that their respondents reported an increase in direct and indirect racial discrimination during the pandemic compared to the time before the pandemic, and racial discrimination during the pandemic was associated with higher anxiety and depression ( 26 ).…”
Section: Introductionmentioning
confidence: 99%